Evaluation of the efficacy of LASER, desensitizing agents, and their combined effect on dentinal hypersensitivity in bicuspids: In Vitro study - Shazia Siddiqui; Keshav K Manglam; Anubha Srivastav; Rehan A Khan; Preeti Rastogi; Samra Shafique (Wolters Kluwer Medknow Publications, 2024)
Aim: This study aimed to know the potential of diode light amplification by stimulated emission of radiation (LASER) and desensitizing agents on blocking the dentinal tubules, which may further help in reducing the most common dental problem named dentinal hypersensitivity (DH). Materials and Methods: Sixty human permanent bicuspids were selected, and preparation was performed in the cervical region measuring 2.5 mm × 2.5 mm × 2.5 mm, followed by acid etching for 15 seconds. These are then divided according to the groups mentioned: group 1-nano-hydroxyapatite (HA) was applied for 15 minutes; group 2-biosilicate was applied for 15 minutes; group 3-diode LASER application was performed twice for 60 seconds in noncontact mode; group 4-nano-HA plus diode LASER application; and group 5-biosilicate plus diode LASER application. The same procedure was followed on the 1st, 7th, and 14th days and then rinsed and stored in artificial saliva, and the saliva was changed every 24 hours. The dentinal tubular occlusion was observed under a scanning electron microscope (SEM) after the 14th day. Result: The maximum dentinal tubular occlusion was observed in group 4, where nano-HA and diode LASER application was performed. Conclusion: All the investigated treatment groups have promising occluding potential, but the maximum was found in group 4 >group 5 >group 3 >group 1 >group 2. LASER plus desensitizing together prove to be potent and effective in reducing dentinal tubular diameter.